Modal decomposition of output field for holographic mode field generation in a multimode fiber channel - Amphawan, Angela; O'Brien, Dominic (2010)
Recent adaptive holographic equalization experiments in multimode fiber demonstrate the advantage of the rapid reconfiguration speed of the spatial light modulator in mitigating modal dispersion, the principal source of bandwidth limitation in MMF. Despite the suppression of a large number of modes, power modal coupling still manifests within the channel. In this paper, a noninterferometric modal decomposition technique was adapted for quantifying the amount of power modal coupling between the modes, for a holographic equalization experiment with a priori modal electric field input. The derivation of the objective function, simulation of binarized holograms and experimental work on intensity measurements at the MMF output are presented.